Rooster Cogburn [videorecording (DVD)] : and the lady - Millar, Stuart, 1929-2006; Wayne, John, 1907-1979; Hepburn, Katharine, 1907-2003; Jordan, Richard, 1937-1993; Zerbe, Anthony, 1936-; McIntire, John, 1907-1991; Portis, Charles (Universal Studios, 2003)
A rough-edged deputy marshall teams up with a strait-laced missionary to track down a band of murdering bank robbers. During the pursuit of the outlaws, a warm rapport develops between the rough-and-tumble lawman and the flinty reverend's daughter.